Myoepithelial carcinoma of buccal mucosa: A rare tumor - Jeevan Lata; Fahad Ahmad; Vimal Chand (Wolters Kluwer Medknow Publications, 2014)
Myoepithelial carcinoma is a rare neoplasm of salivary glands that account for < 1% of all salivary gland tumors. The most common sites of involvement are major salivary glands mainly parotid gland. Intraorally, it can arise from minor salivary glands; palate is the most common site of occurrence. It also occurs in nasopharynx, paranasal sinuses, nasal cavity and larynx in head and neck region. Myoepithelial tumors were first described in 1943. Their malignant variant, myoepithelial carcinoma, was first reported by Stromeyer et al., in 1975, characterized by distinct morphologic heterogeneity and an infiltrative growth pattern into adjacent tissues. Here, we report a rare case of a 55-year-old female with myoepithelial carcinoma of buccal mucosa. It was also rare because of unusual location of tumor. Our patient was treated with wide local resection and remained free of disease for 15 months.